Noise Distraction and Mental Practice in Closed and Open Motor Skills. Issue 1 (August 2014) - Jeon, Hyunjeong; Kim, Jingu; Ali, Asif; Choi, Sungmok
Two experiments were conducted to investigate whether mental practice can serve as an effective intervention strategy for decreasing interference effects of distracting noise at the time of executing open (badminton service return) and closed (badminton serve) skills. In Experiment 1, 44 male students participated and in Experiment 2, 36 students participated. In both experiments, students were randomly assigned to one of three groups: (a) mental practice, (b) mental practice plus noise distraction (MPD), and (c) control. All participants performed 40 trials in the acquisition phase and 20 trials in the retention phase. Absolute error and adjusted variable error were recorded to measure performance. Experiment 1 showed that for a closed skill, the MPD group served with greater accuracy than did the control group in both acquisition and retention phases. Experiment 2 showed that for the open skill, the MP group performed with less error than did the control group, but only in the acquisition trials. Results indicate that mental practice may function to block out noise disturbances and that mental practice may work differently with different skill sets.